Travel Writing and the Desert - Roslynn Haynes (2019)
The European stereotype of the desert as a flat, sandy waste derived from images of the Sahara and the Arabian Desert, the two deserts most familiar in the West. Yet deserts are found in every continent except Europe, and this geographic spread produces an immense variation in desert locations (coastal, inland), landscapes (sandy, salt, clay pan, rocky, mountainous, glaciated), rainfall (from zero recorded in the Atacama Desert to erratic flooding in the Australian deserts), stability (deserts have appeared and disappeared over time), and climate (hot, temperate, cold and ice-bound Antarctica – the most extensive of all deserts). Irrespective of this physical diversity, the very word ‘desert’ involves powerful emotional and cultural associations. Derived from the Latin desertum, meaning ‘abandoned’, it suggests alienation and foreboding, connotations echoed in the word for desert in many languages. The numerous accounts of travellers struggling through extremes of heat or cold, facing starvation, thirst, disorientation, and loneliness, reinforce this image, while the sense of immensity, of visual emptiness, the lack of temporal references in a seemingly changeless landscape, and the characteristic silence of deserts present a further psychological challenge, raising profound questions about identity and meaning. However, these same qualities that many travellers find threatening have proved alluring for others. Precisely because of its visual desolation, its lack of material comforts and distractions, the desert may also engender a sense of the numinous, promoting inner reflection, spiritual inquiry, purification, and visionary enlightenment. Conceivably, a desert landscape beneath a vast monochromatic sky may suggest a unified cosmos, created by one deity, rather than a diversity of gods or spirits and, significantly, the three major monotheistic faiths, Judaism, Christianity, and Islam, originated in the deserts of the Middle East. For these reasons, desert travel writing is rarely confined to physical ...